The EU's Foreign Policy after the Fifth Enlargement: Any Change in Its Taiwan Policy? - Günter Schucher (German Institute of Global and Area Studies (GIGA), 2007)
On 1 May 2004, the world witnessed the largest expansion in the history of the European Union (EU). This process has lent new weight to the idea of an expanded EU involvement in East Asia. This paper will examine the question of whether there has been a change in the EU's foreign policy with respect to its Taiwan policy after the fifth enlargement. It analyses the EU's policy statements on Asia and China to find evidence. The political behaviour of the EU has not changed, although there has been a slight modification in rhetoric. The EU - notwithstanding its claim to be a global actor - currently continues to keep itself out of one of the biggest conflicts in East Asia. The new members' interests in the East Asia region are too weak to alter the EU's agenda, and their economic priorities are rather linked to the programmes of the EU than vice versa. – – Mit zehn neuen Mitgliedsstaaten erfuhr die Europäische Union (EU) am 1. Mai 2004 ihre größte Erweiterung seit Gründung. Schon der Erweiterungsprozess hatte Vorstellungen genährt, die EU werde ihr Engagement in Ostasien verstärken und könne auch mehr zur Lösung des chinesisch-taiwanischen Konflikts beitragen. Dieser Artikel geht am Beispiel der Taiwanpolitik der EU der Frage nach, ob im Zuge der Erweiterung eine Änderung der Außenpolitik der EU festzustellen ist. Eine Analyse der offiziellen Dokumente lässt keinen grundsätzlichen Wandel erkennen, allerdings eine leichte Modifizierung in der Darstellung des Konflikts. Die EU hält sich trotz ihres Anspruchs, ein globaler Akteur zu sein, auch weiterhin aus einem der größten Sicherheitsprobleme in Ostasien heraus. Die Interessen der neuen Mitglieder in Ostasien sind zu schwach, um die außenpolitische Agenda der EU zu ändern; diese sehen im Gegenteil ihre ökonomischen Belange eher mit der bisherigen EU-Politik verbunden.
Keywords: F13; F51; F59; 300; EU; enlargement; Central and Eastern European countries; foreign policy; China; Taiwan